A turn on fluorescent method for the detection of ferric ions based on the size effect of silver nanoclusters. Issue 7 (9th August 2022) - Gao, Yiming; Cai, Hemeiling; Sun, Jing; Di, Junwei
Abstract: A fluorescence enhancement method is developed for the detection of ferric ions based on the bovine serum protein -protected silver nanoclusters. The fluorescence intensity of silver nanoclusters is greatly dependent on their size. Furthermore, silver clusters can be oxidized in the presence of ferric ions to form silver ions, which results in a change in the fluorescence intensity due to formation of small nanoclusters. Among them, the silver clusters with 30 silver atoms show weak original fluorescence intensity and can be used to detect ferric ions based on enhancement of fluorescence. The proposed fluorescent method exhibits an excellent linear range of 2 × 10 −8 −5 × 10 −5 M, with a detection limit of 10 nM. This strategy shows good potential for the detection of ferric ions in food and environmental samples.